2015
DOI: 10.18632/oncotarget.6633
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D2 contributes to TNF-α-induced epithelial mesenchymal transition and invasionviathe PI3K/GSK-3β/β-catenin pathway in hepatocellular carcinoma

Abstract: Although protein kinase D (PKD) has been shown to contribute to invasion and metastasis in several types of cancer, the role of PKD in the epithelial mesenchymal transition (EMT) of hepatocellular carcinoma (HCC) has remained unclear. We found that PKD2 is up-regulated in HCC and is correlated with the metastasis of HCC. PKD2 positively regulated TNF-α-induced EMT and metastasis of HCC. Mechanistic studies revealed TNF-α-induced PKD2 activation is mediated by the formation of a TNFR1/TRAF2 complex. PKD2 bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…These patients also do not suffer from liver dysfunction (Hogan et al, 2015). Likewise, PKD1 mutations are rarely observed in HCC or cholangiocarcinoma, and there is evidence that PKD2 overexpression is oncogenic in HCC (Zhu et al, 2016). We showed that Pkd1 heterozygosity resulted in reduced hepatocyte death and fibrosis after injury, raising the possibility that these mutations could make the microenvironment less cancer-prone.…”
Section: Discussionmentioning
confidence: 72%
“…These patients also do not suffer from liver dysfunction (Hogan et al, 2015). Likewise, PKD1 mutations are rarely observed in HCC or cholangiocarcinoma, and there is evidence that PKD2 overexpression is oncogenic in HCC (Zhu et al, 2016). We showed that Pkd1 heterozygosity resulted in reduced hepatocyte death and fibrosis after injury, raising the possibility that these mutations could make the microenvironment less cancer-prone.…”
Section: Discussionmentioning
confidence: 72%
“…Triggers of EMT in HCC. Schematic representation of molecular pathways triggering EMT in HCC development and progression[105,[109][110][111][112][113][114][115].…”
mentioning
confidence: 99%
“…Various systems have been utilized to induce eMT in human Hcc cell lines (33,34). Stimulation of Hcc cells with TnF-α leads to the induction of eMT (35). TnF-α is known to induce eMT alone or in combination with other cytokines such as transforming growth factor (TGF)-β in several cancer types, such as breast cancer, lung cancer and Hcc (19,21,25).…”
Section: Discussionmentioning
confidence: 99%